Kesalahan siswa dalam menyelesaikan soal cerita tentang bangun ruang sisi lengkung menggunakan prosedur newman - Liya Lestari; Ekasatya Aldila Afriansyah (Institut Pendidikan Indonesia, 2022)
The fact that many students still struggle with mathematical concepts like the material of curved side space is what spurred this research. This study set out to investigate the errors that students make when applying Newman's technique to narrative problems with curved side spaces. Methodology for descriptive qualitative research is used. Three students who reside in the village of Radug were selected as samples using the purposive sampling technique from a population of all students who had studied the Constructing Curved Side Space content. Tests, field notes, observations, and interviews are just a few of the data collection procedures used. The steps of data reduction, presentation, and conclusion are the data analysis technique used. According to the study's findings, there were 16% reading errors, 50% problem understanding errors, 33% transformation errors, 55% process skills faults, and 59% writing errors in the final answer. Problem-solving is still a joint task that must be solved, so there is a need for other research that can help analyze mathematical errors. Penelitian ini dilatarbelakangi oleh masih banyaknya siswa yang mengalami kesulitan dalam memahami ide-ide dasar matematika, termasuk ruang sisi lengkung. Penelitian ini melihat kesalahan yang dibuat siswa saat memanfaatkan proses Newman untuk menyelesaikan cerita ruang sisi lengkung. Metodologi penelitian ini adalah deskriptif kualitatif. Purposive sampling digunakan untuk mengambil tiga siswa dari desa Radug sebagai sampel dari populasi semua siswa yang sebelumnya telah mempelajari konten untuk Membangun Sisi Lengkung Ruang. Beberapa metode yang digunakan untuk mengumpulkan data meliputi tes, catatan, observasi, dan wawancara. Teknik analisis data meliputi tahapan reduksi data, penyajian, dan penarikan data. Menurut temuan penelitian, ada 16% kesalahan membaca, 50% kesalahan pemahaman masalah, 33% kesalahan transformasi, 55% kesalahan keterampilan proses, dan 59% kesalahan menulis dalam jawaban akhir. Pemecahan masalah masih menjadi tugas bersama yang harus diselesaikan, maka perlu adanya penelitian lain yang bisa membantu menganalisa kesalahan matematis.